INFLUENCE OF MUSIC ON HUMAN HEALTH AND PSYCHOLOGY (Scientific journal of the Fergana State University, 2024)
This article talks about the factors of influence of music on human health and psyche. In particular, the diversity of Uzbek folk music, its role in our life, and the opinions of scientists about music are highlighted. Also, information is provided about the period when the impact of music on human health began to be studied on a scientific basis.